Characterization of the Simultaneous Decay Kinetics of Metarhodopsin States II and III in Rhodopsin by Solution‐State NMR Spectroscopy1. (6th February 2014) - Stehle, Jochen; Silvers, Robert; Werner, Karla; Chatterjee, Deep; Gande, Santosh; Scholz, Frank; Dutta, Arpana; Wachtveitl, Josef; Klein‐Seetharaman, Judith; Schwalbe, Harald
Abstract The mammalian visual dim‐light photoreceptor rhodopsin is considered a prototype G protein‐coupled receptor. Here, we characterize the kinetics of its light‐activation process. Milligram quantities of α, ε‐15N‐labeled tryptophan rhodopsin were produced in stably transfected HEK293 cells. Assignment of the chemical shifts of the indole signals was achieved by generating the single‐point‐tryptophan to phenylalanine mutants, and the kinetics of each of the five tryptophan residues were recorded. We find kinetic partitioning in rhodopsin decay, including three half‐lives, that reveal two parallel processes subsequent to rhodopsin activation that are related to the photocycle. The meta II and meta III states emerge in parallel with a relative ratio of about 3:1. Transient formation of the meta III state was confirmed by flash photolysis experiments. From analysis of the site‐resolved kinetic data we propose the involvement of the E2‐loop in the formation of the meta III state.